2010
DOI: 10.1016/j.immuni.2009.12.003
|View full text |Cite
|
Sign up to set email alerts
|

The Receptor SIGIRR Suppresses Th17 Cell Proliferation via Inhibition of the Interleukin-1 Receptor Pathway and mTOR Kinase Activation

Abstract: Interleukin-1 (IL-1)-mediated signaling in T cells is essential for T helper 17 (Th17) cell differentiation. We showed here that SIGIRR, a negative regulator of IL-1 receptor and Toll-like receptor signaling, was induced during Th17 cell lineage commitment and governed Th17 cell differentiation and expansion through its inhibitory effects on IL-1 signaling. The absence of SIGIRR in T cells resulted in increased Th17 cell polarization in vivo upon myelin oligodendrocyte glycoprotein (MOG35–55) peptide immunizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
158
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(163 citation statements)
references
References 58 publications
(92 reference statements)
4
158
0
Order By: Relevance
“…Importantly, this study demonstrated that Th17 cell effector function is linked to mTOR-mediated cell proliferation. When fully differentiated WT and Sigirr −/− Th17 cells were treated with IL-1, IL-1-induced mTOR kinase activation was increased in Sigirr −/− Th17 cells compared with WT cells (36). In line with this finding, our results show that MyD88-dependent IL-1 and IL-23 signaling is required for the later stage of Th17 cell proliferation by activating the mTOR signaling pathway.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Importantly, this study demonstrated that Th17 cell effector function is linked to mTOR-mediated cell proliferation. When fully differentiated WT and Sigirr −/− Th17 cells were treated with IL-1, IL-1-induced mTOR kinase activation was increased in Sigirr −/− Th17 cells compared with WT cells (36). In line with this finding, our results show that MyD88-dependent IL-1 and IL-23 signaling is required for the later stage of Th17 cell proliferation by activating the mTOR signaling pathway.…”
Section: Discussionsupporting
confidence: 86%
“…This discrepancy might be related to the fact that MyD88 is an adaptor not only for IL-1R, but also for TLR. SIGIRR, a negative regulator for TLR and IL-1R signaling, has been shown to suppress Th17 cell proliferation (36). Importantly, this study demonstrated that Th17 cell effector function is linked to mTOR-mediated cell proliferation.…”
Section: Discussionmentioning
confidence: 62%
“…Based on these in vivo data, it is obvious that SIGIRR expression levels in the tissue or cells determine the activation threshold of TIR signaling, which in turn restricts the incidence of inflammation, tissue damage, autoimmunity, and cancer. On the other hand, when considering the above in vivo findings, decreased SIGIRR expression upon infectious stimuli supported the idea of a contributory role of SIGIRR down-regulation to achieve maximum induction of TIR signaling, although prolonged SIGIRR down-regulation may be detrimental to the host (6,30). Because SIGIRR expression tended to be recovered after LPS long exposure (Figs.…”
Section: Discussionmentioning
confidence: 52%
“…For example, Sigirr-deficient mice exhibited a dramatic inflammation in dextran sodium sulfate colitis and endotoxin-challenged septic shock models (6). Furthermore, Sigirr-deficient mice were more susceptible to experimental autoimmune encephalomyelitis resulting from hyperactivation of Th17 cells (30). Moreover, Sigirr deficiency in the Apc min/ϩ mouse, a spontaneous intestinal cancer model mimicking the familial adenomatous polyposis syndrome, led to spontaneous colonic polyposis possibly via increased IL-1-and TLRs-induced Akt-mTOR signaling (31).…”
Section: Discussionmentioning
confidence: 99%
“…Although IL-23 levels were not detectable at all and TGF-β was not elevated in Ikkβ Δ mice, both plasma IL-1β and IL-6 were markedly up-regulated in Ikkβ Δ mice. These results provide further evidence for the essential role of IL-1β in Th17 polarization (28,29) and demonstrate that the oversupply of cytokines in vivo was sufficient to overcome lymphocyte apoptosis and induce a strong Th17 polarization of T cells in response to ambient antigens in vivo, although inhibition of IKKβ by ML120B was able to substantially block IL-17 production ex vivo. Furthermore, up-regulation of IL-17 supported the increase in plasma IL-6 as part of a feedback loop (17) together with IL-1β, despite the fact that IL-6 is transcriptionally controlled by NF-κB.…”
Section: Discussionmentioning
confidence: 59%